Wide range tuning of band gap energy of A3B2X9 perovskite-like halides. (June 2019) - Kim, Se-Yun; Yun, Yeonghun; Shin, Seunghak; Lee, Joon Hyung; Heo, Young-Woo; Lee, Sangwook
Abstract: We report the structural, optical, and electrical properties of A3 B2 X9 halides (where A = Cs, methylammonium (MA), formamidinium (FA), or ethylammonium; B = As, Sb, or Bi; X = Cl, Br, or I). Substitution results in tuning of lattice parameters involving crystal structure change, hence tuning of band gap energy, from ~1.9 to ~3.1 eV. Our results on the band gap energy, type, and crystal structure changes by A, B and X site substitution would give very useful information to develop wide band gap light-absorbers for diverse optoelectronic applications, including highly efficient and stable tandem solar cells. Graphical abstract: Unlabelled Image